The impacts of climate change on ecosystem structure and function - Grimm, Nancy B; Chapin, F Stuart; Bierwagen, Britta; Gonzalez, Patrick; Groffman, Peter M; Luo, Yiqi; Melton, Forrest; Nadelhoffer, Knute; Pairis, Amber; Raymond, Peter A; Schimel, Josh; Williamson, Craig E (Frontiers in ecology and the environment, 2013)
Recent climate-change research largely confirms the impacts on US ecosystems identified in the 2009 National Climate Assessment and provides greater mechanistic understanding and geographic specificity for those impacts. Pervasive climate-change impacts on ecosystems are those that affect productivity of ecosystems or their ability to process chemical elements. Loss of sea ice, rapid warming, and higher organic inputs affect marine and lake productivity, while combined impacts of wildfire and insect outbreaks decrease forest productivity, mostly in the arid and semi-arid West. Forests in wetter regions are more productive owing to warming. Shifts in species ranges are so extensive that by 2100 they may alter biome composition across 5-20% of US land area. Accelerated losses of nutrients from terrestrial ecosystems to receiving waters are caused by both winter warming and intensification of the hydrologic cycle. Ecosystem feedbacks, especially those associated with release of carbon dioxide and methane release from wetlands and thawing permafrost soils, magnify the rate of climate change.